New Zealand exports: Pseudosphaeroma Chilton, 1909 (Isopoda: Sphaeromatidae), a Southern Hemisphere genus introduced to the Pacific coast of North America - Bruce, Niel L.; Wetzer, Regina (Zootaxa, 2008)
Collections made along the coast of California have revealed the presence of a species of Pseudosphaeroma Chilton, 1909, a genus common in New Zealand coastal waters. The genus is entirely Southern Hemisphere in distribution, and this record reports the introduction of a species of Pseudosphaeroma into the San Francisco and Central Coast region of California, the first reported occurrence of the genus as an invasive taxon, and the first record of the genus from the Northern Hemisphere. The genus is also recorded for the first time from the Galapagos and Argentina.